Kompensasi sebagai Penentu Kinerja Karyawan UMKM: Studi pada Pertokoan Keramik Pasar Ular Permai Jakarta Utara - Jonathan, Kevin; Handayani, Kristin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The study addresses the impact of Micro, Small, and Medium Enterprises (UMKM) growth in the Ceramic Market of Ular Permai, North Jakarta, emphasizing the pivotal role of employees in business sustainability. Human resources performance quality is scrutinized in light of two main factors: compensation and motivation. Compensation variables encompass salary, allowances, incentives, and facilities, while motivation variables include physiological, safety, love, esteem, and self-actualization needs. Performance indicators span goals, standards, feedback, tools/facilities, motives, and opportunities. Utilizing a questionnaire distribution method among 33 respondents, the research employs validity tests, reliability tests, descriptive analysis, classic assumption tests, and multiple linear regression analysis. Data processing utilizes IBM SPSS Statistics. Findings reveal that compensation significantly and positively impacts employee performance, whereas motivation does not significantly influence it. Recommendations advocate for transparent compensation systems and facilities enhancement to optimize performance, recognizing the pivotal importance of compensation and motivation in ensuring workers deliver their best at Ular Permai Market.